Evaluation of the "contact-challenge method" in social work practice education : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy at Massey University, Albany, Auckland, New Zealand - Napan, Ksenija (Massey University, 1998)
This thesis examines the importance of integrating theory, practice and experience which is considered to be essential for effective social work education. We live in a globally interconnected world and a holistic and ecological worldview has been utilised to explore relevant theories as well as research in order to develop a method of teaching and learning which attempts to continually improve social work education. Two studies were conducted in order to evaluate and further improve the Contact-Challenge Method. The main aim of the method is to utilise the personal experiences of students, their communication with social work clients, skills training and field work experience in order to help them better integrate theories learnt during social work education. Action research has been used as a research method for evaluation and further development of the Contact-Challenge Method because of its participatory and empowering nature. It is argued that education, social work and research are inevitably value laden and that social work students need to examine their own value base in order to develop a value base for effective social work. It is also argued that social work education has to reflect those values, which arc prescribed by the Code of Ethics of the profession. Learning theory, skills training and the student's personal experience are equal elements of social work education. Values and principles that permeate social work practice should be utilised in the teaching-learning process of social work. The Contact-Challenge Method evaluated in this thesis is focused on modelling social work values and on maximising student-student learning as well as learning from clients and their families. Three theories have been used in the development of evaluation of this method: Experiential Learning Theory, Choice Theory and Adult Learning Theory (Andragogy). The principles and ideas of these three theories have been incorporated in the Contact-Challenge Method and have been carried through in practice in both studies, in Croatia and in Aotearoa- New Zealand. Research into student learning and motivation as well as on the transfer of skills learned in laboratory settings to practice, provided valuable findings that helped in the development and evaluation of the Contact-Challenge Method. Throughout the thesis learning is understood to be a holistic process. In both studies students learned on many levels using cognition, emotions, prior experiences and their theoretical knowledge. Social work education has the advantage that students may learn simultaneously about content and process. Students were expected to take responsibility for their own learning and for creating quality time with their clients. This contributed to the effective integration of theory, practice and experience and to the utilisation of problem solving processes in order to attain learning outcomes set at the beginning of the course. The basic assumptions of this thesis are that: Social work clients and social work practitioners are irreplaceable source of knowledge and practice wisdom for social work students. Setting individual outcomes in the process of learning encourages students to take charge of their own learning. Focusing only on intellectual work in social work schools and only on practical work in social work practice placements cannot produce competent social workers. This thesis proposes an integrative approach to teaching and learning social work where theory, practice and experience are integrated in order to produce change in knowledge, skills, values and attitudes. At the same time it provides a context where students' individual learning outcomes can be achieved and the quality of life of social work clients can be improved.
Keywords: Social work students; Learning theory